Disruption of PF4/H multimolecular complex formation with a minimally anticoagulant heparin (ODSH) - Joglekar, Manali V.; Diez, Pedro M. Quintana; Marcus, Stephen; Qi, Rui; Espinasse, Benjamin; Wiesner, Mark R.; Pempe, Elizabeth; Liu, Jian; Monroe, Dougald M.; Arepally, Gowthami M. (Thrombosis and Haemostasis, 2012)
Recent studies have shown that ultra-large complexes (ULCs) of platelet factor 4 (PF4) and heparin (H) play an essential role in the pathogenesis of heparin-induced thrombocytopenia (HIT), an immune-mediated disorder caused by PF4/H antibodies. Because antigenic PF4/H ULCs assemble through non-specific electrostatic interactions, we reasoned that disruption of charge-based interactions can modulate the immune response to antigen. We tested a minimally anticoagulant compound (2-O, 3-O desulfated heparin, ODSH) with preserved charge to disrupt PF4/H complex formation and immunogenicity. We show that ODSH disrupts complexes when added to pre-formed PF4/H ULCs and prevents ULC formation when incubated simultaneously with PF4 and UFH. In other studies, we show that excess ODSH reduces HIT antibody (Ab) binding in immunoassays and that PF4/ODSH complexes do not cross-react with HIT Abs. When ODSH and unfractionated heparin (UFH) are mixed at equimolar concentrations, we show that there is a negligible effect on amount of protamine required for heparin neutralisation and reduced immunogenicity of PF4/UFH in the presence of ODSH. Taken together, these studies suggest that ODSH can be used concurrently with UFH to disrupt PF4/H charge interactions and provides a novel strategy to reduce antibody mediated complications in HIT.Presented in part at the 52nd American Society of Hematology Annual Meeting and Exposition, December 6th, 2010, Orlando, Florida, USA.
Keywords: Platelet factor 4/PF4; ODSH; heparin and HIT; immunogenicity